Effect of nitrogen sources and phosphorus fertilizer places of application on phosphorus utilization from single super phosphate by wheat (Triticum aestivum L.) - Boaretto, Antonio Enedi; Neptune, André M. Louis; Patella, José Francisco (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1985)
Brazil (CENA/USP, Piracicaba, SP) joint with 15 others country, shared a large research program about wheat fertilization, co-ordinated by A.I.E.A. One aim of this program, which is related here, was to value the phosphorus utilization from single superphosphate by wheat, affected by places of application and nitrogen sources. The experiment was carried out in a red-yellow Podzol with 9 ppm of P. The nitrogen sources are: ammonium sulphate, nitrate and urea, N-rate = 120 kg/ha, half at planting and the remainder at the tillering stage. The single superphosphate - 32P, P2O5-rate = 30 kg/ha, was applied in two places: with the seeds or with the N-sources, 5 cm depth and 2 cm on the ride of the seeds. The wheat was harvested after tillering stage but before heading stage. In the dry mather were determined: % P total, % 32P and percentage of phosphorus utilized (% UP). The nitrogen fertilization reached the % UP, but the nitrogen sources effects were equal. The % UP were equal in the two methods of application of phosphorus fertilizer and ranged within 12 to 19%.